2022
DOI: 10.5194/bg-19-2699-2022
|View full text |Cite
|
Sign up to set email alerts
|

Estimating dry biomass and plant nitrogen concentration in pre-Alpine grasslands with low-cost UAS-borne multispectral data – a comparison of sensors, algorithms, and predictor sets

Abstract: Abstract. Grasslands are an important part of pre-Alpine and Alpine landscapes. Despite the economic value and the significant role of grasslands in carbon and nitrogen (N) cycling, spatially explicit information on grassland biomass and quality is rarely available. Remotely sensed data from unmanned aircraft systems (UASs) and satellites might be an option to overcome this gap. Our study aims to investigate the potential of low-cost UAS-based multispectral sensors for estimating above-ground biomass (dry matt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…The great deal of fundamental research incorporated into the mechanistic PaSim model has ensured satisfactory estimates, which are also comparable to published grassland modeling studies [68,69]. This is relevant considering that simulations for grasslands are generally less accurate compared with arable crops [70] since large uncertainties in biomass and LAI measurements cause simulation of grassland vegetation dynamics to be difficult to perform [67,71].…”
Section: Model Parameterisationmentioning
confidence: 62%
“…The great deal of fundamental research incorporated into the mechanistic PaSim model has ensured satisfactory estimates, which are also comparable to published grassland modeling studies [68,69]. This is relevant considering that simulations for grasslands are generally less accurate compared with arable crops [70] since large uncertainties in biomass and LAI measurements cause simulation of grassland vegetation dynamics to be difficult to perform [67,71].…”
Section: Model Parameterisationmentioning
confidence: 62%
“…The majority of studies considered in this review (more than 65%) reported using rotary-wing platforms to collect data, and quadcopters were the most frequently employed (45-67%) platform (Figure 2). The eBee UASs (developed by senseFly, Swiss, Switzerland) was the commonly used fixed-wing UAS to estimate the AGB [34,48,[70][71][72]. It does not come as surprise that most of the studies reported using DJI drones (DJI Inc., Shenzhen, China) (Phantom 3, Phantom 4, Matrice 100, Matrice 200, and Matrice 600) as the platform of choice to carry RGB [11,17,32,73], multispectral (MS) [45,72,[74][75][76][77], hyperspectral (HS) [78][79][80], and LIDAR [81][82][83] sensors.…”
Section: Uas Platform Typementioning
confidence: 99%
“…Presently, cost-effective unmanned aerial vehicles (UAVs) are developing technologies in the estimation of grasslands parameters. In addition to providing high-spatial-resolution imagery, UAVs are also less subject to cloud and haze interference, making them suitable for measuring grassland aboveground biomass and biochemicals (Franceschini et al, 2022 ; Schucknecht et al, 2022 ). For instance, Schucknecht et al ( 2022 ) evaluated the effectiveness of UAV-borne multispectral data for determining dry biomass and nitrogen (N) concentration of pre-Alpine grasslands.…”
Section: Multispectral Sensors In Estimating Foliar C ...mentioning
confidence: 99%
“…In addition to providing high-spatial-resolution imagery, UAVs are also less subject to cloud and haze interference, making them suitable for measuring grassland aboveground biomass and biochemicals (Franceschini et al, 2022 ; Schucknecht et al, 2022 ). For instance, Schucknecht et al ( 2022 ) evaluated the effectiveness of UAV-borne multispectral data for determining dry biomass and nitrogen (N) concentration of pre-Alpine grasslands. The authors produced a relative root mean square error (average cross-validated) rRMSE cv of 12.6 % for dry biomass and rRMSE cv of 14.2 % for N model using the raw reflectance and vegetation indices.…”
Section: Multispectral Sensors In Estimating Foliar C ...mentioning
confidence: 99%
See 1 more Smart Citation